2023
DOI: 10.1002/ejic.202300167
|View full text |Cite
|
Sign up to set email alerts
|

Six‐Membered NHC Stabilized Monomeric Zinc Complexes

Abstract: This paper describes the rare use of a 6‐membered saturated N‐heterocyclic carbene (NHC) known as 1,3‐di(2,6‐diisopropylphenyl) tetrahydropyrimidine‐2‐ylidene (abbreviated as 6‐SIDipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6‐SIDipp and ZnX2, which resulted in a range of new monomeric 6‐SIDipp⋅ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6‐SIDipp⋅Zn(Et)Br (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…A similar trend was observed for 15 N NMR resonances for 9−11, which are more slightly shifted toward high field (∼−171 ppm) compared to values recorded for 1−3 (∼−169 ppm), further proving enhanced ITr → Zn σ-donation for molecules 9−11. 36 The formation of the cationic species was evidenced by 19 9), Br (10), and I ( 11)] instead of twocoordinated monomers were obtained (Scheme 1 and Figure 4). Although for 10 the X-ray diffraction analysis gave lowquality data, which prevents a detailed discussion of structural parameters for this complex, all molecules 9−11 feature both a rare trigonal planar coordination mode and a cationic nature, uncommon for carbene complexes of zinc.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend was observed for 15 N NMR resonances for 9−11, which are more slightly shifted toward high field (∼−171 ppm) compared to values recorded for 1−3 (∼−169 ppm), further proving enhanced ITr → Zn σ-donation for molecules 9−11. 36 The formation of the cationic species was evidenced by 19 9), Br (10), and I ( 11)] instead of twocoordinated monomers were obtained (Scheme 1 and Figure 4). Although for 10 the X-ray diffraction analysis gave lowquality data, which prevents a detailed discussion of structural parameters for this complex, all molecules 9−11 feature both a rare trigonal planar coordination mode and a cationic nature, uncommon for carbene complexes of zinc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This comprehensive study showed that besides the parent molecule [ZnCl 2 (7-Dipp)], further congeners, bearing, e.g., alkynyl, H-, or THF ligands, can be isolated. A high degree of structural variability associated with low-coordinated Zn II molecules stabilized by different N -heterocyclic carbenes (NHC) is further demonstrated by the recent works of Mondal et al and Gour et al, who prepared trigonal-planar Zn II complexes using fluorenyl-substituted NHC and six-membered NHC, respectively. , Another important class of low-coordinated Zn II complexes bearing NHC ligands represents neutral diorganyl compounds of the type [ZnR 2 (NHC)], first reported by Arduengo et al and comprehensively studied by Dagorne and co-workers (Figure B). These complexes, stable under an inert atmosphere, are readily accessible in high yields by adding the respective NHC to the ZnR 2 precursor, offering a straightforward source of trigonal planar zinc­(II) molecules. Another advantage is an easy modification of the coordination sphere using alkyl ligand abstraction or exchange to give additional trigonal planar derivatives or even two-coordinated complexes (Figure B).…”
Section: Introductionmentioning
confidence: 99%
“…Six-membered N-heterocyclic carbenes have occasionally been used as ligands, [15][16][17][18][19][20] though their applications have steadily grown in recent times. [21][22][23][24] However, these examples mainly include carbenes with bulky groups at nitrogen protecting the ligated metal or main group element. For example, a complex of borane with a six-membered NHC having two 2,6diisopropylphenyl groups has recently been described.…”
mentioning
confidence: 99%